RAPOC : the Rosseland and Planck opacity converter. A user-friendly and fast opacity program for Python - Mugnai, Lorenzo V; Modirrousta-Galian, Darius (arXiv.org, 2022)
RAPOC (Rosseland and Planck Opacity Converter) is a Python 3 code that calculates Rosseland and Planck mean opacities (RPMs) from wavelength-dependent opacities for a given temperature, pressure, and wavelength range. In addition to being user-friendly and rapid, RAPOC can interpolate between discrete data points, making it flexible and widely applicable to the astrophysical and Earth-sciences fields, as well as in engineering. For the input data, RAPOC can use ExoMol and DACE data, or any user-defined data, provided that it is in a readable format. In this paper, we present the RAPOC code and compare its calculated Rosseland and Planck mean opacities with other values found in the literature. The RAPOC code is open-source and available on Pypi and GitHub.